Teaching infection control: an experimental study in Nursing undergraduate studies (Research, Society and Development, 2020)
The objective was to analyze the impact of the theoretical and practical approach on the level of knowledge about infection control of students in the nursing course at a federal university in northern Brazil. A teaching intervention was carried out with a theoretical (40 hours) and practical (40 hours) component through a Situational Strategic Planning in the experimental group. Students who had a theoretical and practical approach had a higher level of knowledge about infection control and felt better prepared to work in the area when compared to students who had only the theoretical content or did not have formal discipline in the curriculum. The importance of inserting infection control content in health care courses is emphasized through a formal approach that will provide students with meaningful learning on a topic relevant to any area of professional practice.